LEAN SUPPLY CHAIN MANAGEMENT MODEL FOR BEST PRACTICE - Anwar, Umari Abdurrahim Abi; Rani, Asni Mustika; Adwiyah, Rabiatul; Aspiranti, Tasya (FEB Universitas Sam Ratulangi Manado, 2023)
Abstract. In Indonesia, the automotive industry is still the pillar of the manufacturing sector. However, the automotive industry faces major challenges, especially in developing environmentally friendly automotive products and supply chains for domestic and global needs. The EV supply chain is becoming more challenging to mass-produce. This research will develop a model that will lead to a lean supply chain in the EV industry in Indonesia as an effort to develop EV in the world. Qualitative descriptive research with a case study approach is used in this study. Case studies on five companies in the EV industry in Indonesia were selected for investigation by collecting various kinds of information from annual reports and other literature which were then processed to obtain a solution so that the problems revealed could be resolved. Lean supply chain management systems are able to add value for customers and for the business and are customer driven. In addition to developing the supply chain on the production side, the accessibility of electricity supply must also be considered when EVs are widely used by the public. Abstrak. Di Indonesia, industri otomotif masih menjadi penopang sektor manufaktur. Namun industri otomotif menghadapi tantangan besar, terutama dalam mengembangkan produk dan rantai pasok otomotif ramah lingkungan untuk kebutuhan domestik dan global. Rantai pasokan kendaraan listrik menjadi lebih menantang untuk diproduksi secara massal. Penelitian ini akan mengembangkan model yang akan mengarah pada lean supply chain pada industri EV di Indonesia sebagai upaya pengembangan EV di dunia. Penelitian deskriptif kualitatif dengan pendekatan studi kasus digunakan dalam penelitian ini. Studi kasus terhadap lima perusahaan industri EV di Indonesia dipilih untuk diselidiki dengan mengumpulkan berbagai macam informasi dari laporan tahunan dan literatur lainnya yang kemudian diolah untuk mendapatkan solusi sehingga permasalahan yang terungkap dapat diselesaikan. Sistem manajemen rantai pasokan yang ramping mampu memberikan nilai tambah bagi pelanggan dan bisnis serta didorong oleh pelanggan. Selain pengembangan rantai pasok di sisi produksi, aksesibilitas pasokan listrik juga harus diperhatikan ketika EV banyak digunakan oleh masyarakat.